Ectropion of the Lower Lip Following Deep Burns an Approach to Correction - C. P. Sawhney (Indian Journal of Plastic Surgery, 1986)
Recurrence of deformity after correction of the ectropion of the lower lip is fairly common. It can be prevented by slight over-correction and use of proper splints for 6-9 months in the post-operative period. Design of one such splint and the results have been discussed.